Irbesartan‐loaded electrospun nanofibers‐based PVP K90 for the drug dissolution improvement: Fabrication, in vitro performance assessment, and in vivo evaluation. Issue 27 (31st March 2015) - Adeli, Ehsan
ABSTRACT Irbesartan with a low bioavailability is known as a poorly water‐soluble drug. The purpose of this investigation is the improvement of physicochemical properties (such as solubility and dissolution rate) of Irbesartan using electrospun nanofibers‐based solid dispersion preparation. Nanofibers were prepared using certain weight ratios of the drug and polyvinylpyrrolidone K90 (PVP K90). Then, dissolution studies were carried out. Moreover, selected samples were examined by many different tests such as Fourier transform infra red (FTIR), differential scanning calorimetry (DSC), X‐ray diffraction (XRD), high‐performance liquid chromatography (HPLC), and scanning electron microscopy (SEM). Though solubility and dissolution rate of all Irbesartan‐PVP nanofibers improved, but the best result was obtained through of ENSD5 (3% (w/v) : 7% (w/v)). In sink condition approximately 97% of this sample was released during 60 min. The drug content was among the different batches from 40.55 ± 1.01 to 245.32 ± 1.77 μg/mL. The maximum saturation solubility was belonged to this sample. According to the results of the thermal analysis and FTIR spectroscopy, there is no chemical reaction between drug and carrier, also samples has not changed during the process. Amorphous structure for nanofibers was confirmed by DSC thermograms and XRD diffractograms and morphological structure of samples were observed by SEM images. Ultimately, in vivo studies were performed in healthy grey rabbits and the results were satisfactory. The drug–polymer nanofibers showed an increase in relative bioavailability than the plain Irbesartan suspension. © 2015 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 2015, 132, 42212.